SOCIO-CULTURAL ASPECTS OF THE PHENOMENON OF INTERNET-ADDICTION - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. The article attempts to implement the socio-philosophical reflection of the phenomenon of Internet-addiction. Analysing the Internet as a social phenomenon, the author wants to highlight the peculiarities of the social space being formed through the network. There is a certain rivalry of realities, social and virtual, which has not become antagonistic yet, but is rather acute when it comes to a man, and problems of social identity in cyberspace. The aim of the article is to make a social-philosophical analysis of some aspects of virtualization of the human living space in the conditions of the Information society, which determine the development and formation of the phenomenon of online addiction. The author sets the task of systematizing domestic and foreign experience in deter-mining the social components that influence the formation of the phenomenon of Internet addiction. Research methods: The article uses the method of comparison, descriptive method and method of system analysis. Research results. The author stresses the rele-vance of the study of the phenomenon of Internet addiction, describes the impact of the Internet on the formation of Internet addictive behavior of man. Among the features that attract users to "live" online, one can distinguish: anonymity, accessibility, invisibility, and plurality of social roles, security, and the ease of use. Among the factors that contribute into the formation of dependence on the Internet the leading place is given to social factors. The most attractive among them is the anonymity of communication and the ability to exper-iment with their own identity. It has been also emphasized the negative social consequences of the active use of the Internet, which leads to the destruction of sociability; cause the social isolation of person. One of the leading aspects of virtualization of individual life is escapism. The desire to escape from reality, to be free from the need for decision-making, taking on responsibility, labor, etc. Strangely enough, but the desire to "escape from reality" is typical of socially and economically well-off societies. A man who does not need to struggle for survival or a high idea, being in a state of material well-being and freedom, however, chooses another life, full of extreme feelings and passions. Discussion. The social functions of the network, which are intended to promote the growth communications between users, are the basis of the formation of the phenomenon of Internet addiction. Accordingly, the reasons why users access to the network, which are prone to Internet-addictive behavior, will have a communicative character: communication, learning, entertain-ment and others. The development of information and communication technologies, mass consumer culture, sociopolitical and econom-ic transformation, changing attitudes and values lead to the emergence of Internet addiction, which appears as a social and cultural issue of our time. By fulfilling the social and communicative function, the Internet acts as one of the conditions for the formation of dys-functional consequences - Internet addiction. Conclusion. The transformation of various spheres of public life, due to the influence of the Internet, caused the interest and attention of researchers from different fields of knowledge, mainly due to the ambiguity of influence and the manifestation of both positive and negative social consequences of the active use of the Internet. When Internet-addictive be-havior destroys sociability, there is a social separation due to the incompleteness of the participation of individuals and groups in the life of society, and dominated by informal social practices. That is, there is a departure to social isolation. Society loses its historical func-tions associated with the process of socialization of the person.